End-of-life care following leg amputation in patients with peripheral artery disease or diabetes. Issue 1 (14th October 2019) - de Mestral, C; Hsu, A T; Talarico, R; Lee, D S; Hussain, M A; Salata, K; Al-Omran, M; Tanuseputro, P
Abstract: Background: The aim was to characterize end-of-life care in patients who have had a leg amputated for peripheral artery disease (PAD) or diabetes. Methods: This was a population-based retrospective cohort study of patients with PAD or diabetes who died in Ontario, Canada, between 2011 and 2017. Those who had a leg amputation within 3 years of death were compared with a control cohort of deceased patients with PAD or diabetes, but without leg amputation. The patients were identified from linked health records within the single-payer healthcare system. Place and cause of death, as well as health services and costs within 90 days of death, were compared between the amputee and control cohorts. Among amputees, multivariable regression models were used to characterize the association between receipt of home palliative care and in-hospital death, as well as time spent in hospital at the end of life. Results: Compared with 213 300 controls, 3113 amputees were less likely to die at home (15·5 versus 24·9 per cent; P < 0·001) and spent a greater number of their last 90 days of life in hospital (median 19 versus 8 days; P < 0·001). Amputees also had higher end-of-life healthcare costs across all sectors. However, receipt of palliative care was less frequent among amputees than controls (inpatient: 13·4 versus 16·8 per cent, P < 0·001; home: 14·5 versus 23·8 per cent, P < 0·001). Among amputees, receipt of home palliative care was associated with a lower likelihood of in-hospital death (odds ratio 0·49, 95 per cent c.i. 0·40 to 0·60) and fewer days in hospital (rate ratio 0·84, 0·76 to 0·93). Conclusion: Palliative care is underused after amputation in patients with PAD or diabetes, and could contribute to reducing in-hospital death and time spent in hospital at the end of life. Graphical Abstract: This was a population-based study of end-of-life care and health costs in amputees with peripheral artery disease or diabetes. Palliative care was underused after major amputation, and may contribute to reducing in-hospital death and time spent in hospital at the end of life. Plea for more palliative care